Lessons in biostatistics (Past, Present, and Future of Statistical Science, 2014)
Today’s medical journals are full of factual errors and false conclusions arising from lack of statistical common sense. Reflecting on personal experiences, I argue that statisticians can substantially improve medical science by informed application of standard statistical principles. Two specific areas are identified where lack of such input regularly produces faulty research. Statisticians are needed more than ever to bring rigor to clinical research.